Fiscal policy sustainability, economic cycle and financial crises: The case of the GIPS - Gabriella Deborah Legrenzi; Costas Milas (Center for Economic Studies and ifo Institute (CESifo), 2012)
We extend previous work on the sustainability of the government's intertemporal budget constraint by allowing for non-linear adjustment of the fiscal variables, conditional on (i) the sign of budgetary disequilibria and (ii) the phase of the economic cycle. Further, our endogenously estimated threshold for the non-linear adjustment is not fixed; instead it is allowed to vary over time and during financial crises. Our analysis presents particular interest within the current economic scenario of financial crises, poor growth and debt crises. Our empirical analysis, applied to the GIPS, shows evidence of a threshold behaviour for the GIPS, that only correct large unbalances, which, in the case of Greece and Portugal, are higher than the EGSP criteria. Financial crises further relax the threshold for adjustment: during financial crises, only very large budgetary unbalances are corrected.
Keywords: H63; H20; H60; C22; 330; debt sustainability; fiscal adjustment; nonlinear models